2003
DOI: 10.1016/j.cub.2003.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Switching between Microtubule- and Actin-Based Transport Systems in Melanophores Is Controlled by cAMP Levels

Abstract: We conclude that the switching of pigment granules between the two major cytoskeletal systems is independent of the densities of MT or AF but is tightly controlled by signaling events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 46 publications
7
129
1
2
Order By: Relevance
“…Because the same seems true here, virus particles may be recruiting a complete bidirectional transport apparatus similar to one used in those systems. Significantly, in two of the previously described systems, there is a key difference: in the melanophores, transport is controlled by a global signal (cAMP͞PKA) whereas, for the lipid droplets, a globally acting directionality factor (Halo) determines the amount of plus-end motion of all lipid droplets in the embryo (44,45). In contrast, global changes in the infected cell are not responsible for differential capsid motion during egress versus entry: the ability of capsids newly deposited into the axon during superinfection to undergo typical retrograde motion indicates that local changes in capsid structure modulate appropriate targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Because the same seems true here, virus particles may be recruiting a complete bidirectional transport apparatus similar to one used in those systems. Significantly, in two of the previously described systems, there is a key difference: in the melanophores, transport is controlled by a global signal (cAMP͞PKA) whereas, for the lipid droplets, a globally acting directionality factor (Halo) determines the amount of plus-end motion of all lipid droplets in the embryo (44,45). In contrast, global changes in the infected cell are not responsible for differential capsid motion during egress versus entry: the ability of capsids newly deposited into the axon during superinfection to undergo typical retrograde motion indicates that local changes in capsid structure modulate appropriate targeting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, during aggregation of melanosomes in mouse melanocytes and Xenopus laevis melanophores, the dynein/microtubule system counteracts the MyoVa/actin system, forcing the melanosomes to switch from the actin to the microtubule network so they can be transported toward the cell center (3,57). In contrast, when melanosomes disperse toward the cell periphery, the MyoVa/actin system wins over the dynein/microtubule system and switches melanosomes to the actin network (3,38,58). However, regulatory mechanisms that govern the directionality of the transport between the two cytoskeletal networks remained unclear.…”
Section: Microtubules Compete Efficiently For Mlph Binding In the Prementioning
confidence: 99%
“…Similarly, synaptic stimulation in Aplysia neurons strongly enhanced the transport of Ap-eEF1A mRNAs to axonal processes, while its transcripts accumulated around the nucleus when the stimulation was restricted to the cell body (Giustetto et al, 2003). Conceivably, activity-mediated tagging of cytoskeleton structures by PKA or another activity-dependent kinase might enhance the transport of mRNAs and proteins to dendrites containing those synapses recently stimulated (Kotz and McNiven, 1994;Luo, 2002;Rodionov et al, 2003;Sanchez et al, 2000). Interestingly, recent studies in cultured neurons have demonstrated that post-Golgi membrane trafficking is polarized toward specific dendrites and small Golgi outposts partition selectively into longer dendrites and concentrate at branchpoints (Horton et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%